Relationships between Knowledge, Sanitation and Hygiene of Food Handlers, and Food Safety in the Restaurants in Pasir Panjang, Kupang, East Nusa Tenggara, Indonesia - Yohanes Karolus Tokan; Yeni W. Astutik; Adrianus Samba; Fany A. Djubida; Dorthea I. Lakahena; Sertulus L. Mali; Eka M. Rahmawati; Marylin S. Junias (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The hygiene factor of the food handler or manager, commonly called personal hygiene, is a very important procedure in maintaining the cleanliness of safe and healthy food management. Hygiene procedures are clean behaviors to prevent contamination of the managed food. This study aimed to determine sanitation hygiene behavior based on food handlers' knowledge on food safety at restaurants in the working area of the Pasir Panjang Puskesmas (Community Health Center). Subjects and Method: A cross-sectional study were conducted in the working are of Pasir Panjang Health center, Kupang, East Nusa Tenggara in December, 2022. A total of 47 restaurants were selected for this study. The dependent variable was food safety. The independent variables were the knowledge and sanitizing hygiene attitude of the handler. The data were collected using questionnaires, and analyzed using Chi-square. Results: There is a significant relationship between knowledge (p< 0001) and behavior (p< 0.001) with food handler hygiene and food safety. Conclusion: knowledge and behaior were associated with food handler hygiene and food safety. Keywords: knowledge, behavior, food handlers, food sanitation hygiene. Correspondence: Yohanes K. Tokan. Master’s Program of Public Health. Universitas Nusa Cendana. Jl. Adi Sucipto Penfui, Penfui, Maulafa, 85001, Kupang, East Nusa Tenggara, Indonesia. Email: yohanes91carolus@gmail.com. Mobile: +62 812-9597-9745.